Analisis perpindahan panas dan konversi energi pada sistem air conditioner tipe split - Wati, Dian Anisa Rokhmah; Wasono, Jami’ul Adi (KOLECER Scientific Journal of Mechanical Engineering, 2025)
Split-type air conditioning systems are widely used to meet thermal comfort requirements, particularly in tropical regions. The performance of these systems is strongly influenced by the mechanisms of heat transfer and energy conversion occurring during the refrigeration cycle. This study analysed the heat transfer processes and energy conversion mechanisms in a split-type air conditioning system under actual operating conditions. A descriptive–analytical method with a case study approach was employed, involving direct observation, measurement of operational parameters, and technical interviews. The observed parameters included refrigerant temperature and pressure, as well as the performance of the primary refrigeration components, namely the evaporator, compressor, condenser, and expansion valve. The results indicate that cooling in a split-type air conditioner is achieved by transferring thermal energy from indoor air to the outdoor environment, with the assistance of electrical energy converted into mechanical work by the compressor. Each system component was found to play an interdependent role in determining heat transfer effectiveness and overall energy conversion efficiency. Stable operating conditions of refrigerant pressure and temperature were observed to influence system performance significantly. This study provides a comprehensive understanding of the operational characteristics of split-type air conditioning systems from the perspective of heat transfer and energy conversion. It may serve as a basis for improving energy efficiency and optimising air conditioning system performance.